Emotional job demand, work-family conflict and emotional exhaustion: a study of a public hospital in China - Peixin Gan (2019)
The aim of the present study is to investigate the level of emotional exhaustion in medical staff of a public hospital in China and also to examine the relationship among emotional job demand,work-family conflict and emotional exhaustion. Data were collected through self-report questionnaires (N=280), targeting groups of medical staff in the hospital. The findings indicate that there is a high level of emotional exhaustion in medical staff respondents in this study. The result also shows that work-family conflict mediates the relationship between emotional job demand and emotional exhaustion. Management implications of the findings, limitations, and suggestions for future research are discussed.